Neuro ICU Procedure Atlas - Jallo, Jack I. (Thieme Medical Publishers, Incorporated, 2020)
Atlas provides insightful guidance on how to perform core procedures in the neuro ICU Neuro ICU Procedure Atlasby distinguished neurosurgeons Jack I. Jallo and David F. Slottje is a visually rich, step-by-step atlas describing technical aspects of common bedside procedures performed in patients with grave neurological conditions. With contributions from an impressive group of contributors, the book features 13 chapters encompassing fundamental techniques, such as shunt externalization/shunt tap, lumbar puncture, lumbar drain, ICP monitor, PbtO2and JvO2 monitors, central and arterial line, cerv.